Harmony in Diversity: An Exploration of Peaceful Coexistence between Muslim and Christian Communities in Aceh, Indonesia - Mawardi Mawardi; Hasni Hasni; Deni Miharja; Busro Busro (UIN Sunan Gunung Djati, 2023)
In this age of globalization and social complexity, the peaceful coexistence of Muslim and Christian Communities in Pertabas Village, Simpang Kanan District, Aceh Singkil District is an important research topic. This study investigates the factors influencing peaceful coexistence between Muslim and Christian communities and identifies effective strategies and approaches to promote religious tolerance and harmony in Pertabas Village. The research method is a qualitative case study involving interviews, observation, and documentation. Significant findings indicate that cooperation in education, economy, and social affairs are concrete manifestations of civil coexistence between Muslim and Christian communities in Pertabas Village. In support of peaceful coexistence between Muslim and Christian communities are the role of the government, clans' similarities, and economic ties. This study contributes to how cooperation and mutual respect between religious groups can form harmonious social and religious relations by encouraging additional research on the factors that influence the establishment of peaceful coexistence in a society with multiple religions. Further research can be conducted to deepen the understanding of the factors that influence the peaceful coexistence of Muslims and Christians in other areas.